Investigation of an attack on the multi-prime RSA cryptosystem based on cubic equations - Aleksėjus Michalkovič; Jokūbas Žitkevičius (Lietuvos Matematikos Rinkinys)
In this paper we consider a modification of the attack on the classic RSA cryptosystem aimed at factoring the public modulus n, which is a product of three primes. To improve the performance of the modified attack we introduce additional parameters. We present the theoretical upper bound on the search range parameter and define a shifting parameter based on the empirical results. Since these changes make our attack probabilistic, we investigate the dependence of the success on the values of the newly defined parameters.